Creation of Network on the Esoko platform to monitor beneficiaries and information dissemination - Asare-Kyei, Daniel; Nikoi, Gordon; Mensah, Mauricia (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Esoko was able to create a network of 256,981 and provided them with Climate Information Services and Climate Smart Agriculture (CIS-CSA).